Biomimetic human bone marrow tissues: models to study hematopoiesis and platforms for drug testing. (2nd November 2021) - García-García, Andrés; Martin, Ivan
ABSTRACT: We propose an in vitro 3D culture system combining perfusion bioreactors, scaffolds and human primary cells to engineer fully-humanized, biomimetic and customizable bone marrow tissues. This system could serve as a model to investigate human hematopoietic stem cell niches, but also as a drug testing platform for pharmaceutical research and patient-personalized medicine.